DESAIN PROTOTYPE ALARM DAN PEMADAN KEBAKARAN OTOMATIS MENGGUNAKAN ARDUINO DENGAN KONTROL JARAK JAUH (Jurnal Riset Teknik Komputer, 2025)
Fires have the potential to cause significant material losses and even loss of life. Addressing this issue requires a system that can detect and respond automatically. The purpose of this research is to design and build a prototype automatic fire alarm and extinguishing system using a remote-controlled Arduino. This system functions to activate the alarm and automatically activate the extinguishing mechanism when a fire is detected. Furthermore, the system is equipped with a remote control for real-time monitoring and control of the device. Test results demonstrate that the prototype is capable of providing a fast and effective response, as expected. Therefore, this system is a practical, economical, and easy-to-implement alternative for fire prevention, both in households and small-scale industries.